A Bibliometric Analysis of Islamic Financial Literacy for Future Research - Suwarsono, Bambang; Idris, Ahmad (Jurnal Cendekia Keuangan, 2025)
Introduction/Main Objectives: This study is to provide a wider bibliometric literature review on Islamic financial literacy (IFL). Background Problems: IFL requieres a comprehensive review of existing studies. Looking for potential topics is one way to develop knowledge in IFL by using bibliometric studies. Novelty: This paper is to fill in the gaps by providing an extensive bibliometric analysis of the literature related to IFL. Research Methods: We analyzed 57 articles published from 2016 until 2024, a 9 year period. Articles were taken from the Scopus database. We studied classify articles using VOSviewer software. We analyzed citation and analysis co-occurrence. Finding/Results: The topic of IFL is still in demand today. Indonesia and Malaysia are the countries with the most productive in terms of the number of documents. Six thematic clusters: The red clusters include demographic variables, financial inclusion, financial literacy, halal, Islamic banking services, Islamic capital market, Islamic Finance, and Islamic financial literacy. The green cluster includes COVID-19, Finance, human, literacy, self-concept, and self-efficacy. The blue cluster includes banking, intention to use, Islamic financial inclusion, and marketing. The yellow cluster includes behavioural intention, Islamic banking, Islamic financial services, and Islamic marketing. The orange cluster include intention, market discipline, sharia mutual funds, and subjective norm. The purple cluster include financial socialization and religiosity. The following topics have attracted the greatest attention: Islamic Financial Inclusion, Islamic Capital Market, Halal, Religiosity, Self-Concept, and Self-Efficacy. Research limitation/implications: This paper highlights the interconnectedness of education, personal behavior, and financial products within the Islamic finance framework. This structured breakdown aligns the elements that influence Islamic finance development, providing a pathway for examining how literacy, behavior, and products shape the field.